Observations and Electron Density Retrievals of Jupiter's Discrete Auroral Arcs Using the Juno Microwave Radiometer. Issue 9 (11th September 2020) - Hodges, Amorée; Steffes, Paul; Bellotti, Amadeo; Waite, J. Hunter; Brown, Shannon; Oyafuso, Fabiano; Orton, Glenn; Arballo, John; Gladstone, G. Randall; Levin, Steven; Bolton, Scott
Abstract: Jupiter's aurorae reflect microwave radiation emitted upward from Jupiter's atmosphere and downward from the cold sky above due to regions in the auroral plasma with increased electron densities. The lack of thermal radiation from the atmosphere was observed by Juno's Microwave Radiometer (MWR) on overflights of the aurorae during seven different orbits. Out of Juno's first 21 orbits, seven orbits inferred enhanced electron densities in Jupiter's auroral arcs. The most profound disruption in microwave emission was observed during Perijove 5. This perijove demonstrated the most significant cold spot for Channel 1 (0.6 GHz), with cold spots also present in Channels 2 (1.25 GHz) and 3 (2.6 GHz) in a location where the influence of Jupiter's moon, Io, likely increased the electron density in Jupiter's aurora. The maximum electron densities retrieved from Channel 1 are on the order of 3 × 10 9 cm −3, and in the presence of the Io flux tube, electron densities could reach 10 10 cm −3 affecting Channels 2 and 3. Plain Language Summary: As Juno flew over Jupiter's auroral arcs, the microwave emission at the longest wavelength (50 cm) dropped dramatically for seven out of the first 21 orbits due to reflections of the cold sky by the densest sections of the aurorae known as the arcs. The occurrence of microwave reflections requires extraordinarily large electron densities compared to the densities measured in Earth's aurora and the Jovian ionosphere. The retrieval of electron densities presented in this paper provides upper limits for auroral electron densities that are up to 5 orders of magnitude larger than densities in the planet's ionosphere. The strongest of these results was in a location where Jupiter's satellite Io influenced the region's electron density. Key Points: Data from Juno's Microwave Radiometer (MWR) have shown reductions in microwave emission over Jupiter's aurorae A retrieval method has been developed to estimate upper limits for electron densities from the MWR brightness temperatures Upper limits of electron densities are much larger than the observed H 3 + ion densities